Software Development for Transformer Model Supporting Significant Learning Electrical Machines - Gina Rodriguez Borges, Ciaddy; Alberto Perez Rodriguez, Jesus; Danilo Lituma Ramirez, Edgar; Belen Perez Baltar, Ana (International Journal of Psychosocial Rehabilitation, 2020)
In the field of engineering, the execution of practices that allow students to contrast theoretical concepts with practical application is essential, allowing them to establish the relationship of physical variables and their effects on the system. These practices can currently be carried out using simulation systems, known as virtual laboratories, which rely on software that allows us to offer advantages over physical experimentation, and since this requires higher costs, access to equipment that is sometimes unavailable and risks, is one of the significant practices in the electrical engineering career, it is the one concerning the course of electrical machines and particularly the one directed to the design of transformers because the objective of this research focused on the development of a free application software that allows the students to carry out simulations for the design and testing of dry transformers and at the same time the analysis of their behavior, facilitating the comparison with the installed and commercially available transformers with an allowable error margins of less than 8%.